Reproductive fitness and genetic risk of psychiatric disorders in the general population - Niamh Mullins (Nature Portfolio, 2017)
Why genetic variants that confer risk for psychiatric disorders persist in the genome is an evolutionary conundrum. Here, Mullinset al. report association of polygenic risk for autism with having fewer children and polygenic risk for ADHD with higher reproductive fitness.